2015
DOI: 10.1007/7854_2015_411
|View full text |Cite
|
Sign up to set email alerts
|

Noradrenergic–Dopaminergic Interactions Due to DSP-4–MPTP Neurotoxin Treatments: Iron Connection

Abstract: The investigations of noradrenergic lesions and dopaminergic lesions have established particular profiles of functional deficits and accompanying alterations of biomarkers in brain regions and circuits. In the present account, the focus of these lesions is directed toward the effects upon dopaminergic neurotransmission and expression that are associated with the movement disorders and psychosis-like behavior. In this context, it was established that noradrenergic denervation, through administration of the sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 95 publications
0
1
0
Order By: Relevance
“…In this sense, preclinical data from MPTP mice and marmosets suggest that damaging the LC leads to a loss of DA neurons in the SNc followed by more pronounced motor deficits (Mavridis et al, 1991;Marien et al, 1993;Bing et al, 1994;Fornai et al, 1995;Fornai et al, 1997;Yao et al, 2015;Li Y. et al, 2018). Conversely, the damage produced by MPTP is reduced when the synthesis of NA is boosted (Kilbourn et al, 1998;Archer, 2016) or the NET is knocked out (Rommelfanger et al, 2004). A recent publication using mutant mice characterized by the progressive degeneration of dopaminergic neurons demonstrated that chronic pharmacological NET blockade ameliorates such degeneration and the subsequent motor impairment (Kreiner et al, 2019).…”
Section: Noradrenaline Neuroinflammation and Neuroprotectionmentioning
confidence: 99%
“…In this sense, preclinical data from MPTP mice and marmosets suggest that damaging the LC leads to a loss of DA neurons in the SNc followed by more pronounced motor deficits (Mavridis et al, 1991;Marien et al, 1993;Bing et al, 1994;Fornai et al, 1995;Fornai et al, 1997;Yao et al, 2015;Li Y. et al, 2018). Conversely, the damage produced by MPTP is reduced when the synthesis of NA is boosted (Kilbourn et al, 1998;Archer, 2016) or the NET is knocked out (Rommelfanger et al, 2004). A recent publication using mutant mice characterized by the progressive degeneration of dopaminergic neurons demonstrated that chronic pharmacological NET blockade ameliorates such degeneration and the subsequent motor impairment (Kreiner et al, 2019).…”
Section: Noradrenaline Neuroinflammation and Neuroprotectionmentioning
confidence: 99%